Research methods for children - Nabors, Laura Anne (Nova Publisher's, 2013)
Research with children is an invaluable way to tell their story in their own words. Research documenting ideas about children from parent and teacher perspectives is valuable, but in itself, does not tell the story from the child s point of view. Thus, the purpose of this book is to develop a book for those interested in conducting research with children, to document their voices and perceptions.